Energy Router for Peer-to-Peer Trading Under Emergency With Energy Traceable Functionality - Yu Nie; Yixuan Zhang; Yihua Hu; Mohammed Alkahtani; Mohammed Alquraish; Hui Xu (IEEE Access, 2025)
Multi-port bidirectional energy router is an important infrastructure for peer-to-peer (P2P) energy trading after power supply interruption. The state-of-the-art multi-port bidirectional energy router lacks the traceability function of an energy source. A triple active bridge (TAB) converter with partial power processing (PPP) progress is employed as multi-port bidirectional energy router. This proposed multi-port bidirectional energy router integrates the energy conversion and signal transmission in one converter, which supports peer-to-peer trading. In detail, the controlling approach of power transmission and the phase perturbation modulation (PPM) method of signal transmission, which realize the energy traceable functionality, are also illustrated in this paper. Finally, Simulation is performed and presented as proof of the feasibility of the designed method.